Respuesta :

Answer:

y = 4/3

Step-by-step explanation:

y = 3^x+1

Substitute -1 for x.

y = 3^(-1)+1

y = 1/3 + 1

y = 1/3 + 3/3

y = 4/3

Answer:

If this was your equation [tex]y=3^x+1[/tex] then the answer is 4/3.

If this was your equation [tex]y=3^{x+1}[/tex] then the answer is 1.

Step-by-step explanation:

It is basically asking us to replace x with -1 and find y.

If [tex]y=3^x+1[/tex] and we plug in -1 for x, we get [tex]y=3^x+1=3^{-1}+1=\frac{1}{3}+1=\frac{4}{3}[/tex] .

If [tex]y=3^{x+1}[/tex] and we plug in -1 for x, we get [tex]y=3^{x+1}=3^{-1+1}=3^0=1[/tex].